A study on the thermal sintering process of silver nanoparticle inkjet inks to achieve smooth and highly conducting silver layers. Issue 6 (7th March 2016) - Vandevenne, Glen; Marchal, Wouter; Verboven, Inge; Drijkoningen, Jeroen; D'Haen, Jan; Van Bael, Marlies K.; Hardy, An; Deferme, Wim
Abstract : Silver nanoparticle inkjet inks are commonly used to print electrically conductive patterns, such as sensors or electrodes in organic light emitting diodes (OLEDs) or organic photovoltaic devices (OPVs). After printing, a sintering step is required to transform the printed layer into an electrically conductive one. Gaining more insight into the occurring phenomena during this post‐treatment step is necessary when applying different kinds of inkjet ink. Therefore, in this work the commercially available silver nanoparticle inkjet ink Metalon JS‐B30G from Novacentrix is characterised during the different stages in the printing and thermal sintering sequence. The pre‐printing and post‐sintering characterisation proves that the inkjet ink used has got the right material parameters, such as viscosity and particle size. Silver layers with sheet resistances of 40 mΩ/sq were obtained with an average roughness lower than 10 nm. The experiments performed show the different stages during the thermal sintering procedure. Based on this, suitable thermal sintering parameters are defined leading to application of these conductive silver layers in OLEDs.